Intracellular distribution of chromium and toxicity on growth in Chlorella pyrenoidosa - Hörcsik, Zsolt Tibor; Balogh, Árpád (Acta Biologica Szegediensis, 2002)
The effect of chromium on the growth response on green alga Chlorella pyrenoidosa were examined. An increase in chromium concentration caused a significant reduction in the growth of Chlorella cells, and the the EC50value was 1.6 mg/L, while lethal concentration of chromium appears to be approximately 20 mg/L. We have investigated the intracellular distribution of chromium, and the elementel composition of the treated cells. Bulk of the chromium is localized in the cell wall, while the membrane and soluble fraction contains the smaller part of the total chromium.